Changements institutionnels en éducation supérieure: Un nouveau paradigme? - Tremblay, Andre; Paquette, Sylvie (Canadian Journal of Higher Education, 2000)
With globalisation, higher education in Quebec has suffered the same budget cuts as other public sectors. But does this mean that a more fundamental change will occur — a paradigmatic change? We begin by comparing Canadian university financing with that of other OECD countries. We then go on to look at the long term evolution of Canadian provincial financing, more specifically Quebec. We then analyse the situation of each Quebec university from the point of view of three theoretical models: Clark's collegiality, Ouchi's modes of control and Niklasson's paradigmatic analysis. We conclude with an analysis of the Quebec Ministry of Education's orientation within a longer temporal framework. In North America, Quebec seems to have an original model, even within the context of budget cuts. Strong links with the private sector are favoured. The private sector is occupying an increasingly larger place in financing, which also seems to confer a special position to the universities. Different from more globalising countries, they are conceived not as part of high-tech industrial development rather the Universities are seen as a support for national industries which are in turn part of the larger trends of economic and technological globalisation.